The technology of making cheese from camel milk (Experimental biology, 2015)
This paper shows a process diagram of obtaining cheese made from camel milk using starter Camifloctm. Also studied the physicochemical parameters of camel milk and organoleptic properties, the performance of the product
Keywords: camel milk; cow milk; cheese; starte; CamiflocTM.